An investigation into opportunities to practice english outside the classroom: The case of office workers as EFL learners in Can Tho city - Kiều, Thị Ngọc Dung (Trường đại học Cần Thơ, 2019)
The study is conducted for three primary aims. Firstly, it aims to investigate opportunities office workers as EFL learners are aware of to practice English outside the classroom; Secondly, the challenges office workers face in making use of these opportunities to practice English; Finally, strategies office workers use to obtain these opportunities to practice English.